1999
DOI: 10.1590/s0004-27491999000500005
|View full text |Cite
|
Sign up to set email alerts
|

O uso da mitomicina C em cirurgia combinada

Abstract: Objetivo: Avaliar a eficácia e a segurança do uso intra-operatório da mitomicina C (MMC) em cirurgias combinadas (facectomia extracapsular + trabeculectomia).Métodos: Vinte e quatro pacientes foram randomizados para cirurgia combinada com MMC (0,5 mg/ml) (n = 14) ou solução salina (n = 10) por 3 minutos.Resultados: Após 12 meses de seguimento, a PIO média do grupo que recebeu MMC (13,2 ± 2,9 mmHg) foi significativamente menor que a observada no grupo controle (16,3 ± 3,9 mmHg) (p = 0,02). O número médio de med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…In 1983 mitomycin C was first described as a potent fibroblast inhibitor in filtration surgery. Since then, several authors have reported excellent results with its intraoperative use, especially in refractory glaucoma (19) . This suggests that cyclophosphamide could also be used in filtration surgery as a substitute to mitomycin.…”
Section: Discussionmentioning
confidence: 99%
“…In 1983 mitomycin C was first described as a potent fibroblast inhibitor in filtration surgery. Since then, several authors have reported excellent results with its intraoperative use, especially in refractory glaucoma (19) . This suggests that cyclophosphamide could also be used in filtration surgery as a substitute to mitomycin.…”
Section: Discussionmentioning
confidence: 99%
“…Its antimitotic action inhibits the formation of DNA, acting only in dysplastic epithelium. 13 An attenuation of conjunctival epithelium, stroma with loosely organized collagen, few blood vessels and rare inflammatory cells in histopathological 1 7 21 60 90 Total* Keratitis 73 ----73 Edema of eyelid 26 ----26 Wound dehiscence -27 ---27 Ischemia ------Recurrence ---7 -7 TOTAL 99 27 ---133 * Eyes TABLE 3 Postoperative complications in untreated eyes with 5-fluorouracil.…”
Section: Discussionmentioning
confidence: 99%
“…O menor número de pacientes com PO menor que 15 mmHg sem medicação e a menor freqüência de complicações observados no nosso estudo, possivelmente, decorreu do fato de termos utilizado MMC na concentração de 0,2 mg/ml ao passo que Joos et al utilizaram MMC a 0,5 mg/ml (4) . Costa et al observaram baixamento médio de 5,3 mmHg após 12 meses de seguimento nos pacientes submetidos a FEC/TREC com MMC a 0,5 mg/ml (5) . Acreditamos que a MMC a 0,2 mg/ml seja mais segura em cirurgias combinadas primárias.…”
Section: Os Prontuários De 46 Pacientes (53 Olhos) Submetidos à Cirurunclassified